Frequency and potential risk factors associated with the development of asymptomatic T2 hyperintense cervical spine lesions on MRI in patients with relapsing-remitting multiple sclerosis - Fadlallah, Yasser; Wang, Yujie; Malik, Muhammad Taimur; Tian, Fan; Calabresi, Peter A; Izbudak, Izlem; Huang, Yishang; Fitzgerald, Kathryn C; Mowry, Ellen M (Multiple sclerosis, 2025)
Spinal cord (SC) imaging is less routinely used for monitoring disease activity in patients with multiple sclerosis (MS), and the frequency of clinically silent breakthrough SC disease remains unclear. The objective was to determine the frequency of asymptomatic T2 hyperintense cervical SC (c-SC) lesions in patients with relapsing-remitting MS (RRMS) and identify associated risk factors. We included RRMS patients aged 18-65 years followed at the Johns Hopkins MS Center (2014-2019), with up to four brain and c-SC magnetic resonance imaging (MRI) scans considered per patient. New asymptomatic lesions were identified as hyperintense T2 lesions on MRI during routine surveillance. Univariate and multivariate logistic regression identified factors associated with developing asymptomatic lesions on the first scan, and a generalized estimating equations model assessed factors across successive scans. Among 869 patients included, the proportion of asymptomatic lesions identified ranged from 4.8% to 12.1% across scans. Roughly half of those with c-SC lesions also showed new brain lesions. Patients receiving higher-efficacy therapies were more likely to have an asymptomatic lesion detected (odds ratio (OR) = 1.48, 95% confidence interval (CI) = 1.16-1.88, = 0.001), as were Black/African American individuals (OR = 1.64, 95% CI = 1.23-2.18, = 0.001). These findings suggest a limited but important role for c-SC imaging, especially for Black/African Americans who may benefit from routine surveillance.